Mengubah Wawasan & Peran Guru dalam Era Kesejahteraan - Karim Karhami (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: In era which is full of change, where culture, characteristic, and environment of learning ever change, teacher must face it with the change too, not with old patterned thinking and act. Old view about â€œwhat is the teacherâ€, â€œ what is the learnerâ€ â€œwhat is learningâ€ and â€œ what is teachingâ€ that positioned teacher as the most knowledgeable, most skillful side, and student as the most unknowledgeable, learning identical with writing and listening teachers speech, have to be changed. this old view positioned teacher as â€˜teaching workerâ€™ require to be shifted to new view by placing teacher at role as â€˜worker of conceptor and creator process to learnâ€™. Its meaning, teacher positioned as â€œfacilitatorâ€ than â€œdestroyerâ€ â€œlearningâ€ event, while student played the part as â€˜producerâ€™ (â€˜architectâ€™ idea constructor â€™ than only as â€˜idea consumerâ€™ ( â€˜beggarâ€™ idea).